CHARACTERISTICS OF WHITE CORN NOODLE SUBSTITUED BY TEMPEH FLOUR [Karakteristik Mi Jagung Putih dengan Substitusi Tepung Tempe] - Nur Aini; V. Prihananto; S. Joni Munarso (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
Different corn type and processing of corn flour can produce flour with different physical and chemical characteristics. Processing of such flour into noodle will also result in different properties of noodle. While substitution of corn flour with tempeh flour can improve the protein content of the noodle it also impair its sensory characteristics. The objectives of this research were to determine the best combination of corn flour-type, corn flour processing and proportion of corn:tempeh flour to produce the best corn noodles based on physical, chemical and sensory properties. The observed variables of this study were moisture, ash, soluble protein, fat, elongation, colour, flavour, taste, and preferences. The results showed that based on physical, chemical and sensory properties, the best corn noodle could be made from flour made from waxy corn soaked for 24 hours and a ratio of corn:tempeh flour of 80:20. The noodle produced had 12.1% of total protein content, 2.8% of soluble protein, 8.4% of fat, 5.9% of moisture, 3.6% of ash, 69.9% of carbohydrate, 17.6% of elongation, yellow colour, slight flavour of corn/soybean, and 2.6 of preferences.